Design of hole repair system for wireless sensor networks based on triangle partition. Issue 4 (11th November 2021) - Wu, Daqin; Hu, Haiyan; Xie, Zheng
Aiming at the problems of low coverage, high redundancy and low repair efficiency in the current design methods of network hole repair system, a design method of wireless sensor network hole repair system based on triangular partition method is proposed. The location and shape of holes in the bottleneck area of wireless sensor networks are determined; the best interior points of the hole edge in the bottleneck area are obtained, and the moving direction and distance of sensor nodes in wireless sensor networks are calculated; the best interior points are selected according to the results of calculation, and the holes in the bottleneck area of wireless sensor networks are self-repaired. The experimental results show that the coverage level of the proposed method is always higher than 80%, and the redundancy can be stabilised below 20%, laying a foundation for the further application of wireless sensor networks in practice.